Enhancement of photoresponsive electrical characteristics of multilayer MoS2 transistors using rubrene patches - Cho, Eun Hei; Song, Won Geun; Park, Cheol Joon; Kim, Jeongyong; Kim, Sunkook; Joo, Jinsoo (Nano research, 2015)
Multilayer MoS2 is a promising active material for sensing, energy harvesting, and optoelectronic devices owing to its intriguing tunable electronic band structure. However, its optoelectronic applications have been limited due to its indirect band gap nature. In this study, we fabricated a new type of phototransistor using multilayer MoS2 crystal hybridized with p-type organic semiconducting rubrene patches. Owing to the outstanding photophysical properties of rubrene, the device characteristics such as charge mobility and photoresponsivity were considerably enhanced to an extent depending on the thickness of the rubrene patches. The enhanced photoresponsive conductance was analyzed in terms of the charge results of the nanoscale laser confocal time-resolved PL measurements. transfer doping effect, validated by the microscope photoluminescence （PL） and